Հայ մտավորականության դերը քրդական մշակույթի զարգացման բնագավառում (XIX դարի երկրորդ կես) - Չաչանյան, Կառլեն («Զանգակ - 97»)
The paper deals with the progressive role of the Armenian intelligency in the developmenl of Kurdish culture during the second half of the XIX Century. Many Armenian scholars, literators, clergymen were involved in the study of the Kurdish history, ethnography, Armenian-Kurdish relations. Among them the aulhor distinguishes Kh. Abovian, M. Tigranian, M. Momjian, G. Artsrouni, M. Mamourian, M. Khrimian, etc. Due to their efforts had appeared fundamental studies devoted to the Kurdish history, language, poetry, music.
Keywords: Պատմություն; Մշակույթ